'Encroaching upon trade union preserves': the 1950s fight over global labor norms between the international confederation of free trade unions and moral re-armament. (4th July 2021) - Grimm, Kevin E.
ABSTRACT: The clash between the International Confederation of Free Trade Unions, an international labor body that included the AFL and the before CIO, and Frank Buchman's Moral Re-Armament Movement illustrated one of the many intra-Western contests in the early Cold War over creating international norms. Should national labor centers work for a world of more moral interpersonal relationships or should they follow traditional collective bargaining activities? What messages should Western labor actors send to workers in the decolonizing world? Which group could provide the best anti-communist Western model of labor relations? Analyzing CIO executive council meetings, ICFTU executive board and world congress meetings, MRA assemblies in Switzerland, Congress in Stockholm to statements from Indian trade unionists, and the presence of both organizations on the ground in West Africa in the mid-1950s, this article explores one of the ways two international NGOs argued over the content of global labor practices emanating from the West during the early Cold War. Their clash also revealed the anxiety Western unions felt as MRA claims and activities seemed to upset their precarious balancing act of appearing stridently anti-communist while still benefiting workers through collective bargaining, which would undermine the appeal of communism by showcasing a capitalist model where workers benefited.